FAKTOR PENENTU LABA PERBANKAN SYARIAH DI INDONESIA - Mohamad Reza Fauzan; Syafri (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2016)
Banking is an institution that became one of supporting economic activity. Banks also be intermediary institutions that are considered important in financing both for individuals and organizations as well as being an alternative as a place to invest. So that's why many people assess the performance of banks to make a benchmark in the use of banking services. Besides the performance of the banking concern for management to assess whether the bank has been able to carry out normal banking operations and meet all its obligations in accordance with the regulations of both the government and the central bank. This study aimed to obtain results which are then used as an overview of the health of banks. This research was conducted in six Islamic banks in Indonesia. Data used is secondary data in the period 2010-2014. The analytical methods used are panel data analysis. The result showed that the Operating Expense to Operating Income affect a significant negative effect on bank profits while the Capital Adequacy Ratio, Net Performing Financing and Financing to Deposit Ratio significantly the negative and not on the bank's profit.